Pengaruh Kompleksitas Operasi Perusahaan Dan Audit Fee Terhadap Audit Report Lag - Novia Sari; Cherrya Dhia Wenny (MDP Student Conference, 2026)
This study aims to examine the effect of corporate operational complexity and audit fees on audit report lag in consumer cyclicals sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The sampling technique used in this study is purposive sampling, resulting in a total sample of 50 companies. This study employs multiple linear regression analysis as the research method. The results indicate that corporate operational complexity and audit fees have a significant negative effect on audit report lag